ANALISIS PENGELOLAAN BERAS SEMI ORGANIK DI KABUPATEN OKU TIMUR - Munsiarum (Jurnal Bakti Agribisnis, 2015)
The purpose of this research were to: (1) To determine the level of production costs and revenue from the management of semi-organic rice in East OKU District, (2) To analyze whether the management of semi-organic rice in East OKU District to develop. This research was conducted in 3 villages namely Karang Sari, Tegal Rejo, and Sumbersuko. The location determination is done intentionally (purposive) because in the village there is the management of organic rice. The research was conducted in May 2013. The study found that the average total cost of production which acquired the generated business in the year to 1 reception Rp 9.342 million, - / Process, a fee of Rp 4,771,679, - / process then revenue Rp 4,570,303, - / process. Enterprises in the year to 2 reception Rp 10.0602 million, - / Process, a fee of Rp 4,657,624, - / process the revenue of Rp 5,402,576, - / process. Enterprises in the year to 3 reception Rp 13.75 million, - / Process, a fee of Rp 4,675,274, - / process, the revenue of Rp 9,074,726, - / process. Enterprises in the year to 4 reception Rp 20.4 million, - / processes, costs Rp 4,681,574, - / process, the revenue of Rp 15,718,426, - / process and NPV values obtained Comfounding lowest factor of 18% amounting to Rp 25 854 .258, - / 4 years, the value NPVN Comfounding highest factor of 30% was obtained at a negative value - Rp 1,661,258, - / 4 years with an IRR obtained 29.28% and Net B / C gained 1.26, then attempt profitable and feasible to be developed and passed.